The occurrence of cerebrovascular atherosclerosis in Alzheimer’s disease patients - Yuan J (Dove Medical Press, 2013)
Jing Yuan,1,* Ge Wen,2,* Yingjia Li,3 Changxing Liu1 1Department of Medical Information, General Hospital of Jinan Military Command, Jinan, People’s Republic of China; 2Imaging Center, Nanfang Hospital of Southern Medical University, Guangzhou, People’s Republic of China; 3Ultrasound Diagnosis Department, Nanfang Hospital of Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workBackground: Both Alzheimer’s disease (AD) and cerebrovascular atherosclerosis (CA) contributed to dementia in an aged population. Whether they share the same mechanism is unknown.Aim: Our goal was to explore the occurrence rates of CA in AD patients.Method: Here we examined the degree of CA in different groups of AD patients with contrast angiography. Ninety-three AD patients were recruited to the present study. Contrast computed tomography scanning and contrast angiography were performed for CA analyses.Result: We found that the cerebrovascular plaques were common in AD patients, which was partly correlated with the severity of AD (as determined by cognitive decline).Conclusion: We concluded that vascular dementia may partly correlate with AD pathology.Keywords: Alzheimer’s disease, cerebrovascular atherosclerosis, aging, patients